A novel electrocardiogram characteristic in patients with myocardial injury due to COVID-19 - Marzieh Mirtajaddini (Wolters Kluwer Medknow Publications, 2021)
Background: Coronavirus disease of 2019 (COVID-19) is a respiratory disease which can lead to cardiovascular complications including myocarditis, myocardial infarction, and heart failure. Electrocardiogram (ECG) may change in patients with COVID-19 with or without heart involvement. In this study, the ECG changes were evaluated in myocardial injuries due to COVID-19. Methods: This study was done on 22 COVID-19 patients with ST segment elevation in ECG and high troponin level. COVID-19 was confirmed using reverse-transcription polymerase chain reaction test. The ECG variables were evaluated by an expert cardiologist. Statistical analyses were carried out on ECG variables where the significance level of 0.05 was assigned. Results: Of 22 patients, 17 cases (77.3%) were male and 6 cases (27.3%) had a history of coronary artery disease. The most common myocardial involvement was extensive anterior type (31.8%), followed by anterior type (22.7%). Sinus rhythm was observed in 95.5% of patients and 54.5% had low voltage ECG in limb leads. No significant correlation was found between low voltage ECG and demonstrable etiologies of low voltage. Conclusion: The prevalence of low voltage ECG was significantly high in limb leads of patients with myocardial injury due to COVID-19 which was considerably greater than that of myocarditis or myocardial infarction patients.